Generation of Mucosal Anti-Human Immunodeficiency Virus Type 1 T-Cell Responses by Recombinant Mycobacterium smegmatis(▿) - Yu, Jae-Sung (American Society for Microbiology, 2006)
A successful vaccine vector for human immunodeficiency virus type 1 (HIV-1) should induce anti-HIV-1 immune responses at mucosal sites. We have generated recombinant Mycobacterium smegmatis vectors that express the HIV-1 group M consensus envelope protein (Env) as a surface, intracellular, or secreted protein and have tested them in animals for induction of both anti-HIV-1 T-cell and antibody responses. Recombinant M. smegmatis engineered for expression of secreted protein induced optimal T-cell gamma interferon enzyme-linked immunospot assay responses to HIV-1 envelope in the spleen, female reproductive tract, and lungs. Unlike with the induction of T-cell responses, priming and boosting with recombinant M. smegmatis did not induce anti-HIV-1 envelope antibody responses, due primarily to insufficient protein expression of the insert. However, immunization with recombinant M. smegmatis expressing HIV-1 Env was able to prime for an HIV-1 Env protein boost for the induction of anti-HIV-1 antibody responses.